2012 5th IAPR International Conference on Biometrics (ICB) 2012
DOI: 10.1109/icb.2012.6199766
|View full text |Cite
|
Sign up to set email alerts
|

3D face recognition: A robust multi-matcher approach to data degradations

Abstract: Over the past decades, 3D face has emerged as a solution to face recognition due to its reputed invariance to lighting conditions and pose. While proposed approaches have proven their efficiency over renowned databases as FRGC, less effort was spent on studying the robustness of algorithms to quality degradations. In this paper, we present a study of the robustness of four state of the art algorithms and a multi-matcher framework to face model degradations such as Gaussian noise, decimation, and holes. The fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this literature study, its importance in face registration and (or) recognition has particularly an impact for developing an array of smoothing techniques implementing in real time system and illustrating their significance for processing purpose. Reference Description [7] Authors have demonstrated the effect of the median filter for removing sharp spikes, and again interpolation technique has been added to fill the holes on the face image. [8] Authors have compared the performance of landmark localization technique with array of smoothing methods, namely Max Filter, Min filter, Gaussian filter, Mean filter, and Weighted median filter.…”
Section: Introductionmentioning
confidence: 99%
“…In this literature study, its importance in face registration and (or) recognition has particularly an impact for developing an array of smoothing techniques implementing in real time system and illustrating their significance for processing purpose. Reference Description [7] Authors have demonstrated the effect of the median filter for removing sharp spikes, and again interpolation technique has been added to fill the holes on the face image. [8] Authors have compared the performance of landmark localization technique with array of smoothing methods, namely Max Filter, Min filter, Gaussian filter, Mean filter, and Weighted median filter.…”
Section: Introductionmentioning
confidence: 99%